2012
DOI: 10.1007/s13365-012-0103-4
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine activates nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and induces human immunodeficiency virus (HIV) transcription in human microglial cells

Abstract: Human immunodeficiency virus (HIV) primarily infects glial cells in the central nervous system (CNS). Recent evidence suggests that HIV-infected individuals who abuse drugs such as methamphetamine (METH) have higher viral loads and experience more severe neurological complications than HIV-infected individuals who do not abuse drugs. The aim of this study was to determine the effect of METH on HIV expression from the HIV long terminal repeats (LTR) promoter and on an HIV integrated provirus in microglial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 44 publications
5
73
0
Order By: Relevance
“…The nuclear factor-ĸB (NF-κB) signaling is the major pathway that regulates the inflammatory cytokine expression and has been widely studied in inflammatory responses (Kawai and Akira, 2007). Previous studies have reported several stimuli such as lipopolysaccharide (LPS) and METH-induced inflammation in both neuronal cells and glial cells by the overactivation of NF-κB signaling (Flora et al, 2003;Shah et al, 2012;Wires et al, 2012;Perpoonpattana et al, 2013;Coelho-Santos et al, 2015;Jumnongprakhon et al, 2015). Therefore, the inhibition of these negative effects may be beneficial in protecting BBB impairment.…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear factor-ĸB (NF-κB) signaling is the major pathway that regulates the inflammatory cytokine expression and has been widely studied in inflammatory responses (Kawai and Akira, 2007). Previous studies have reported several stimuli such as lipopolysaccharide (LPS) and METH-induced inflammation in both neuronal cells and glial cells by the overactivation of NF-κB signaling (Flora et al, 2003;Shah et al, 2012;Wires et al, 2012;Perpoonpattana et al, 2013;Coelho-Santos et al, 2015;Jumnongprakhon et al, 2015). Therefore, the inhibition of these negative effects may be beneficial in protecting BBB impairment.…”
Section: Introductionmentioning
confidence: 99%
“…We inserted DNA oligonucleotides (Table S2) complementary to gRNAs A−D into a humanized Cas9 expression vector (A/B in pX260; C/D in pX330) (16) and tested their individual and combined abilities to alter the integrated HIV-1 genome activity. We first used the microglial cell line CHME5, which harbors integrated copies of a single round HIV-1 vector that includes the 5′ and 3′ LTRs, and a gene encoding an enhanced green fluorescent protein (EGFP) reporter replacing Gag (pNL4-3-ΔGag-d2EGFP) (17). Treating CHME5 cells with trichostatin A (TSA), a histone deacetylase inhibitor, reactivates transcription from the majority of the integrated proviruses and leads to expression of EGFP and the remaining HIV-1 proteome (17).…”
Section: Resultsmentioning
confidence: 99%
“…We first used the microglial cell line CHME5, which harbors integrated copies of a single round HIV-1 vector that includes the 5′ and 3′ LTRs, and a gene encoding an enhanced green fluorescent protein (EGFP) reporter replacing Gag (pNL4-3-ΔGag-d2EGFP) (17). Treating CHME5 cells with trichostatin A (TSA), a histone deacetylase inhibitor, reactivates transcription from the majority of the integrated proviruses and leads to expression of EGFP and the remaining HIV-1 proteome (17). Expressing of gRNAs plus Cas9 markedly decreased the fraction of TSA-induced EGFPpositive CHME5 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental and clinical evidence indicates that HIV neuropathogenesis and neurocognitive deficits are exacerbated with coexposure to methamphetamine (30)(31)(32)(33). Methamphetamine induces HIV transcription, potentiates HIV protein-mediated oxidative stress pathways in the brain (34), and increases proinflammatory cytokines (35).…”
mentioning
confidence: 99%